A cement-based 1−3 piezoelectric composite sensor working in d15 mode for the characterization of shear stress in civil engineering structures. (15th October 2018) - Ma, Yongli; Cheng, Xiangyang; Jiang, Qinghui; Li, Yingwei
Abstract: This paper reports a cement-based 1−3 piezoelectric composite sensor for the characterization of shear stress in civil engineering structures. The sensor was fabricated using a cutting−filling method, in which the piezoelectric elements work in d 15 shear mode. Its properties—such as piezoelectric constant, dielectric constant, electromechanical coupling coefficient, and density—have been systematically tested. By embedding two sensors into a concrete beam, we have further characterized its performance with a three point bending test technique. Results show that both sensors have very good accuracy, linearity, and frequency bandwidth. For instance, under a dynamic load of 2000 N at 10 HZ, the shear stresses measured by the two embedded sensors were 12.07 kPa and 12.01 kPa, slightly smaller than the calculated value of 12.5 kPa. Furthermore, the potential application of the sensor in monitoring acoustic signals in concrete was validated by knocking three arbitrary points of the beam.